JC virus conversion rates in natalizumab treated patients: the melbourne longitudinal cohort study. Issue 5 (8th May 2017) - Dwyer, Chris; Jokubaitis, Vilija; Baker, Josephine; Haartsen, Jodi; Rath, Louise; Coleman, Jennifer; Fryer, Kylie; Macintyre, Jennifer; Cartwright, Adriana; Skibina, Olga; Macdonell, Richard; Butler, Ernest; et al.
Abstract : Objectives: To analyse John Cunningham virus (JCV) serology in natalizumab treated patients over time and assess whether seroconversion was influenced by natalizumab treatment and prior immunosuppressive therapy. Methods: Patients treated with natalizumab for relapsing-remitting multiple sclerosis at six tertiary hospitals in Melbourne, Australia (n=960) were longitudinally assessed for change in JCV serostatus. Duration of exposure to natalizumab and exposure to prior immunosuppressive therapy was documented. Results: Two hundred and ninety-four patients (30.6%) had positive JCV serostatus when commencing natalizumab while 666 patients (69.4%) were JCV negative. JCV serostatus changed in 148 of 960 longitudinally followed patients (15.4%) over a mean observation period of 2.7 years. Durable positive seroconversion was seen in 81 of 666 initially JCV negative patients (12.2% over 2.7 years, 4.4% per year). Conversely, durable negative seroconversion was seen in 17 of 294 initially JCV positive patients (5.8% in 2.7 years, 2.1% per year). Fluctuating JCV serostatus was seen in 50 of 960 patients (5.2%). Durable positive seroconversion was more common early in therapy with natalizumab, with 31.9% occurring in the first year of exposure. Positive seroconversion rates were not increased in patients who had received prior treatment with methylprednisolone. No positive seroconversion events were documented in patients exposed to mitoxantrone. Conclusions: In contrast to recently published data from colleagues in France and Germany, in our longitudinal cohort study rates of durable positive JCV seroconversion correlate closely with expected background rates of JCV seroconversion in the general population. In addition, JCV seroconversion and positive serostatus is not increased in patients with prior exposure to immunosuppressive agents. The low seroconversion rates seen after the first year of exposure suggests that less frequent JCV testing of natalizumab treated patients may be safe.